(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The important problem of bee collected pollen and beeswax production is cutting of costs and increasing o f working efficiency. Novel technologies o f bee collected pollen drying and beeswax melting is described in the article. Pollen kiln with the air recuirent allows reducing the total energy consumption for drying from 4800W to 670W. It is stated that 2.5cm thick heat insulation of drying box reduces heat losses from 2050W to 190W.Honeycombs melting in the dry-air beeswax melting-house reduce energy consumption to 0.94 kWh/kg wax. The melting temperature t°=130°C disinfects wooden parts of honeycombs and wax. Heat energy losses through melting-house walls is 300W.